Improvement of Science Learning Outcomes of Light Properties Material Through Discovery Learning Model in SD Muhammadiyah Donorejo - Sri Sujiyati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research was motivated by the low learning outcomes of students in science learning grade IV SD Muhammadiyah Donorejo learning year 2020/2021 light properties material. This study aims to improve student learning outcomes and improve teacher performance by using discovey learning models. The implementation of learning improvement research is carried out during two diklus and is carried out through a process of ptk-cycled assessment with four stages (planning, implementation, observation, reflection). From the results of data analysis, the conclusion obtained is that discovery learning models can improve student learning outcomes. This can be seen in the increase in the average asset value of each cycle, at Pre cycle 35%, Cycle 1 50%, Cycle 1I 70%, and cycle III 90%. Thus, based on data analysis, the discovery learning model has been successful even though it is not yet perfect.